Bullous Pemphigoid Mimicking Cellulitis - Ilya Ivyanskiy; Dhara Dave; Anass Dweik; James Yeary; Tarek M. Naguib (SAGE Publishing, 2021)
Bullous pemphigoid (BP) is the most prevalent autoimmune blistering skin disease in the Western world affecting mainly the elderly population. The diagnosis is based on clinical assessment along with specific immunopathologic findings on skin biopsy. Risk factors include genetic factors, environmental exposures, and several infections including hepatitis B, hepatitis C, Helicobacter pylori , Toxoplasma gondi , and cytomegalovirus. A variety of drugs have been associated with BP including but not limited to dipeptidyl peptidase-4 inhibitors, loop diuretics, spironolactone, and neuroleptics. Associated neurologic disorders (dementia, Parkinson's disease, bipolar disorder, previous stroke history, and multiple sclerosis) have also been described. Common clinical presentation consists of extremely pruritic inflammatory plaques that resemble eczematous dermatitis or urticaria, followed by formation of tense bullae with subsequent erosions. Typical distribution involves the trunk and extremities. Mucosa is typically spared affecting only 10% to 30% of patients. Several unusual clinical presentations of BP have been described such as nonbullous forms with erythematous excoriated papules, plaques, and nodules. Other reported findings include urticarial lesions, prurigo-like nodules, multiple small vesicles resembling dermatitis herpetiformis or pompholyx, vegetating and purulent lesions localized in intertriginous areas, and even exfoliative erythroderma. Recognition and management of such cases can present a diagnostic challenge to clinicians. In this article, we describe another variant which to our knowledge is the first case to present with a cellulitis-like presentation in a patient with a known history of BP.